Routinization, within-occupation task changes and long-run employment dynamics - Davide Consoli; Giovanni Marin; Francesco Rentocchini; Francesco Vona (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
The present study contributes to the existing literature on routinization and employment by capturing within-occupation task changes over the period 1980-2010. The main contributions are the measurement of such changes and the combination of two data sources on occupational task content for the United States: the Dictionary of Occupational Titles and the Occupational Information Network. We show that within-occupation task change: i) accounts for 1/3 of the decline in routine-task use; ii) accelerates in the 1990s, decelerates in the 2000s but with significant catching-up; iii) is associated with educational upgrading in several dimensions and iv) allows one to escape the employment decline conditional on initial routine-task intensity.
Keywords: J23; J24; O33; 330; tasks; routinization; technological change; employment dynamics; race between technology and education